Estudo do impacto da viscosidade intrínseca do pet reciclado pós-consumo em embalagens cosméticas - Castro, Paula Junqueira de (2015)
The use of PET in cosmetics packaging is growing and the use of post-consumer recycled material is an alternative with the development of recycling process and also with all the discussions about the increase of environmental impact. The objective of this project is to evaluate the influence of post-consumer recycled PET in the mechanical properties and the aesthetics appearance in cosmetics packaging. The materials used was virgin PET with nominal value of intrinsic viscosity (IV) of 0,80 dL/g and two grades of post-consumer recycled PET with nominal value of IV of 0,68dL/g and 0,80dL/g. The main parameter used in the PET industry is the IV because it is directly related to the molar mass of the polymer and also to the quality of the material. The packages were manufactured by injection stretch blow molding process with different percentages of virgin PET and post-consumer recycled PET. The characterization was realized by visual analysis, spectroscopy to evaluate the variation of color and mechanical tests. The results were satisfactory for the mechanical tests, showing no major differences in results when compared to virgin PET. In aesthetics appearance, the color variation is noticeable, due to the thermal degradation of the material, but less noticeable in the packages with the post-consumer recycled PET with lower IV.